Studies of energy absorption of lattice structures manufactured from PETG filament with FFF 3D printing - Banaszek , Mateusz; Baranowski , Paweł; Płatek , Paweł; Sarzyński , Marcin; Cieplak , Kamil (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper presents experimental and numerical results of the mechanical response of body-centered cubic (BCC) lattice structures manufactured with the fused filament fabrication (FFF) method using polyethylene terephthalate glycol (PETG) material. The BCC structures were subjected to uniaxial compression tests using a universal strength machine with three different values of deformation velocities. Moreover, dog-bone specimens were manufactured in three orientations to identify the PETG mechanical properties, which were supplemented with the literature data of PETG tested under compression. Then, the mechanical properties were correlated in the LS-Dyna code using a visco-plastic material model, which was used to numerically reproduce the experimental uniaxial tensile test conditions. The compression tests of BCC were simulated, and the results of experiments and numerical simulations were compared with satisfactory agreement. It was demonstrated that the properties of the 3D printed PETG varied, depending on both the printing direction and the type of applied load condition (compression/tension). Furthermore, the results also show that for the strut-based lattice structures manufactured with the FFF method and PETG material, it is mandatory to consider the above remark while simulating this type of mechanical behavior in a structure. Additionally, the influence of element type and cross section of the struts was also analyzed in this work. Results presented in the paper confirmed that the BCC lattice structures were effective in terms of energy absorption capacity, and they demonstrated long-range plateau deformation force plots.